European experience in organizing physical education and promoting a healthy lifestyle in educational institutions - Лясота, Тетяна Іванівна; Цибанюк, О. , Сливка, Л. , Батюк, А. (Universidad de Murcia, 2023)
In this article, the European experience of organizing physical education and promoting a healthy lifestyle in educational institutions is analyzed. The research aims to identify the main features of the concepts of physical education and sports that dominated Western Europe in the late twentieth and early twenty-first centuries. It is noted that the basic concepts of physical education and sports of the 1970s in certain countries have been transformed into more balanced ones. It is indicated that the main content of the Bologna declaration is that 47 member countries have committed themselves to bring their educational systems in line with a model that is transparent and easily comparable. This allows for the issuance of European-style diplomas over time. The analysis of the development of PE and sports in Western Europe allows us to draw some conclusions that may be useful for the leaders of various state authorities and sports organizations to improve the system of physical education and sports. Actions aimed at improving the physical fitness of young people, preserving and developing the need for physical activity, increasing the enrollment of students in sports clubs, and participating in competitions are of utmost importance, as they distract young people from various harmful hobbies typical of the academic sphere. © 2023 Universidad de Murcia. All Rights Reserved.
Keywords: Bologna process; European experience; Extracurricular physical activity; Globalization; Physical education; Valeological education